Lost in transformation: The Paris Agreement, the IPCC and the quest for national transformative change - Lidskog, Rolf; Sundqvist, Göran (Frontiers in Climate, 2022)
The IPCC stated in its special report on global warming of 1.5 degree (SR15) that meeting the temperature target of the Paris Agreement requires rapid and far-reaching changes in all aspects of society. This is called a need for transformative change. However, what is meant by transformative change? What should be changed, and how should it be changed? These questions are explored in this paper, which is structured in three steps. First, it develops a conceptual meaning of transformative change that is centered on society. Then, it analyses how the IPCC in SR15 understands transformative change. The analysis finds that the proposed pathways to reach the targets of 2 degrees and 1.5 degrees have a strong technical focus on energy supply, which makes broader and deeper transformative change almost unnecessary. Finally, it turns to the national level, analyzing Sweden’s ambition to become the first fossil-free welfare society in the world. The analysis of Sweden’s climate policy shows that, in line with SR15, Sweden has a restricted focus on changes in energy supply, making transformative change, such as restructuring the economic system and questioning consumption patterns, unnecessary. Based on this analysis of the international (the IPCC) and national (Sweden) levels, the paper finds a need for an elaborated, consistent and deeper understanding of transformative change. It concludes that to be relevant to countries’ work to achieve ambitious climate targets, the IPCC should develop a more qualified understanding of transformative change, which requires a better integration of social science.